A cluster randomised controlled trial investigating the effectiveness of the 'Support group' intervention in primary schools in Norway: A study protocol. - Lisbeth Valla; Bente Sparboe-Nilsen; Lisbeth G Kvarme; Therese Haugerud Bjerketveit; Milada Hagen; Brita Askeland Winje (PLoS ONE)
Bullying is a pervasive public health issue that significantly affects the mental and physical well-being of children, often leading to long-term consequences that persist into adulthood, such as mental health disorders, social isolation, and economic challenges. Despite numerous interventions implemented in schools, bullying remains a persistent problem. The Support Group intervention, based on a solution-focused approach (SFA), aims to address bullying by enhancing peer support and empowering children within the school environment. This study seeks to evaluate the effectiveness of this intervention in reducing bullying and improving class environment, mental health, quality of life, and self-efficacy among 5th-7th grade Norwegian schoolchildren compared to usual care. This cluster randomized controlled trial (RCT) will be conducted in 26 primary schools across three municipalities in central-eastern Norway. Schools will be randomized to either the intervention group, which will implement the Support Group intervention, or the control group, which will continue with usual care based on national guidelines. Data will be collected at baseline, post-intervention, and at 6- and 9-month thereafter. A parallel process evaluation will be conducted to assess the fidelity and quality of the intervention's implementation and to identify factors associated with its success. The intervention will be compared with usual care using generalised mixed models for repeated measures. This study will provide crucial insights into the effectiveness of the Support Group intervention in reducing bullying and promoting mental health among schoolchildren. The findings are expected to inform best practices in bullying prevention and contribute to the development of more effective, evidence-based interventions in school settings. The trial outcomes will be pivotal in shaping future strategies for creating safer and more supportive school environments in Norway. The study is registered in Clinical trial registration: Trial registration (NCT) 06578260.